2023
DOI: 10.1007/s11357-022-00717-x
|View full text |Cite
|
Sign up to set email alerts
|

GTP energy dependence of endocytosis and autophagy in the aging brain and Alzheimer’s disease

Abstract: Increased interest in the aging and Alzheimer’s disease (AD)-related impairments in autophagy in the brain raise important questions about regulation and treatment. Since many steps in endocytosis and autophagy depend on GTPases, new measures of cellular GTP levels are needed to evaluate energy regulation in aging and AD. The recent development of ratiometric GTP sensors (GEVALS) and findings that GTP levels are not homogenous inside cells raise new issues of regulation of GTPases by the local availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 153 publications
(199 reference statements)
1
4
0
Order By: Relevance
“…CR1, encoding a type-I transmembrane glycoprotein, is one of the most important risk genes for late-onset AD, playing multiple roles in the onset of AD, such as Aβ clearance, neuroinflammation, and tauopathy (Zhu et al, 2015). Additionally, autophagy disorders were proved to be associated with AD, and our study also identified autophagy-related genes, including ERRB2 and RAB8B, which have been preliminarily confirmed to be associated with the pathogenesis of AD (Wang et al, 2017;Martinez et al, 2023). Growing evidence from clinical and pathological studies indicates the important relationships between the ongoing deterioration of brain cholesterol metabolic disturbance and AD pathophysiology (Vestergaard et al, 2010).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…CR1, encoding a type-I transmembrane glycoprotein, is one of the most important risk genes for late-onset AD, playing multiple roles in the onset of AD, such as Aβ clearance, neuroinflammation, and tauopathy (Zhu et al, 2015). Additionally, autophagy disorders were proved to be associated with AD, and our study also identified autophagy-related genes, including ERRB2 and RAB8B, which have been preliminarily confirmed to be associated with the pathogenesis of AD (Wang et al, 2017;Martinez et al, 2023). Growing evidence from clinical and pathological studies indicates the important relationships between the ongoing deterioration of brain cholesterol metabolic disturbance and AD pathophysiology (Vestergaard et al, 2010).…”
Section: Discussionsupporting
confidence: 67%
“…The Manhattan plot illustrates the AD-associated risk factors in 13 brain regions and blood screened by MR-JTI ( Figure 2 and Supplementary Figure 1 ). Among the top five genes in the brain amygdala region, RAB8B and HLA-DOB have been confirmed to be involved in the pathogenesis of AD ( Figure 2A ; Patel et al, 2021 ; Martinez et al, 2023 ). Strong evidences indicates that abnormalities of CR1, APOC1, APOC2, LACTB, and ABCA7 were closely related to AD ( Figures 2B, C ; Karch and Goate, 2015 ; Shao et al, 2018 ; De Roeck et al, 2019 ; Kulminski et al, 2022 ; Yu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 97%
“…The binding dynamics of EB3, therefore, reflect the presence of GTP-bound tubulin dimers and GTP levels in cells ( 22 ). Cellular GTP level, due to its direct relationship with the Krebs cycle, mitochondria functions, and GTPase activity, is a sensitive indicator of the overall energy status and metabolism of the cell ( 23, 24 ). Therefore, monitoring the highly dynamic EB3-binding process provides a quick and reliable quantification of changes in cellular energetic states that have fast responses to phototoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Although the metabolic changes experienced by senescent cells are poorly understood, the upregulation of oxidative phosphorylation in cluster 3 may point to senescent cells striving to maintain energy production by mitochondria. We also found that the genes involved in regulation of GTPase activity were reduced in cluster 3 and increased in cluster 5; these genes are implicated in membrane trafficking, intracellular vesicle transport, autophagy, and secretory pathways [ 51 ]. In all, cluster 3 senescent cells demonstrate a transcriptome consistent with growth arrest (elevated CDKN2A mRNA, leading to increased p16/pRB activity), while cluster 5 cells show features of DNA damage-induced p53/p21-mediated cellular senescence (developed through cluster 2, which displays high levels of CDKN1A mRNA).…”
Section: Discussionmentioning
confidence: 99%